Analisis Kinerja Keuangan Daerah Tahun Anggaran 2011 – 2015 Di Kabupaten Sumedang Provinsi Jawa Barat - Hafifurrahman Hasan (Jurnal Ilmu Pemerintahan Widya Praja, 2017)
AbstractLocal financial performance is one measure to see the ability of local in the running local autonomy, especially in implementing fiscal decentralization. Seeing this, the authors are interested in doing research with the title "ANALYSIS OF FINANCIAL PERFORMANCE OF FISCAL YEAR 2011 - 2015 SUMEDANG REGENCY WEST JAVA" to measure how much of Sumedang implement fiscal decentralization by looking at the financial performance.The research combines qualitative research to strengthen the quantitative calculation results with sequential explonatory research model (mixed method). Quantitative data analysis carried out by calculating of the local financial performance with the regression analysis to measure the relative influence the independent variable of the financial performance. While the analysis of qualitative data through interviews to the relevant parties to strengthen the results of quantitative measurements.Result showed that the financial performance of Sumedang seen from the calculation shows the ratio of Degree of Fiscal Decentralization less criteria, with an average calculation of 12% over the five-year budget. Regional Financial Independence Ratio shows a instructive relationship. Growth ratio showed an fluctuated. Effectiveness and efficiency ratios showed criteria PAD is very effective and very efficient. Liquidity ratio to the current ratio is 2.87 while the current ratio shows 2.59. And Asset Turnover ratio shows the number of 10%. Based on these research also known factors that significantly influence the financial performance of Sumedang are PAD and Asset whereas Transferhave negatifely significant influence to financial performance with the contribution of the effect of 100%. The Goverment of Sumedang have some efforts done to increase financial performance through socialiszation, Land Value Zona program, repeated data collection, and intensification or extensification of local tax. Keywords: Local Financial Performance, PAD, Transfer.